GATA3 promotes ferroptosis resistance by repressing integrin β1 signaling - Emmet R. Karner; Mengdie Wang; Hira Lal Goel; Arthur M. Mercurio (Proceedings of the National Academy of Sciences, 2025)
Understanding mechanisms that determine the response of cells to ferroptotic stress is a timely issue that has significant ramifications for biology and pathology. We investigated these mechanisms in the context of breast cancer where tumors are composed of diverse populations of cancer cells that differ in their ferroptosis sensitivity. Using single-cell RNA-sequencing, we determined that cancer cell populations with luminal differentiation are more resistant to ferroptosis than other cells within a heterogeneous tumor. Subsequent bioinformatic analysis and experimentation revealed that GATA3, a transcription factor that promotes luminal differentiation, has a causal role in ferroptosis resistance in luminal breast cancer cells. In pursuit of the mechanism involved, we found that GATA3 represses the expression of integrin β1 and its downstream signaling cascade. This observation led us to demonstrate that integrin β1 signaling is necessary for sensitivity to ferroptosis in basal breast cancer cells because it regulates a FAK/ROCK pathway that sustains the expression of ACSL4, a lipid-modifying enzyme that is essential for ferroptosis. The repression of integrin β1 by GATA3 inhibits this signaling pathway, rendering cells ferroptosis resistant. Together, these data provide insight into mechanisms of ferroptosis sensitivity and resistance that are linked to the cell biology and signaling pathways of the diverse types of cells present in breast tumors.